STUDY CORROSION PROCESSES OF OIL EQUIPMENT - E. S. Dremicheva; E. R. Zvereva (Известия высших учебных заведений: Проблемы энергетики, 2018)
The work carried out studies of corrosion processes when in contact with carbon steel aggressive media. As an aggressive environment are considered water-oil emulsions with different concentrations of oil, we revealed the corrosion rates of oil’s dependency concentration.